Local community acceptance of foreign tourists at Kuala Tahan National Park, Pahang - Hilmi, Muhamad Heiqal (2016)
Tourism industry has become the source of income for the local community at Kampung Kuala Tahan for many years. Due to the fast growth of tourism activities, it may bring changes to the local community in Kuala Tahan in the form of sociocultural and economic. In order to understand these changes better, a study has been conducted on their perception and on how they responding to the tourists arrival at their locality. The main objective for the study was to determine the local’s perception on the socio-culture impact of foreign tourist, to determine the local’s perception on the economic impact of foreign tourists at Kuala Tahan and to determine the acceptance level of local community towards foreign tourists at Kuala Tahan. A total of 150 questionnaire have been distributed to the local community at Kg Kuala Tahan by using the convenience sampling for 1 week and the data has been collected. Result of the study demonstrate an encouraging mean for both socio-culture and economic perception of local community. By determine the acceptance level of community towards foreign tourists, the mean value of socio-culture and economic has indicate high acceptance of foreign tourist’s arrival in Kampung Kuala Tahan. Although participation of tourists in tourism activity in Kuala Tahan is increasing every year, locals are able to adapt with arrival of tourists as they are the source of income for most of the community at Kampung Kuala Tahan. Thus, the information that has been obtained from this study may be used as valuable reference to improve the management at Kuala Tahan in the future.